2022
DOI: 10.1186/s13287-021-02697-9
|View full text |Cite
|
Sign up to set email alerts
|

The application of mesenchymal stromal cells (MSCs) and their derivative exosome in skin wound healing: a comprehensive review

Abstract: Recently, mesenchymal stromal cells (MSCs) and also their exosome has become a game-changing tool in the context of tissue engineering and regenerative medicine. MSCs due to their competencies to establish skin cells, such as fibroblast and keratinocyte, and also their unique attribute to suppress inflammation in wound site has attracted increasing attention among scholars. In addition, MSC’s other capabilities to induce angiogenesis as a result of secretion of pro-angiogenic factors accompanied with marked an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(109 citation statements)
references
References 179 publications
0
106
0
3
Order By: Relevance
“…Some studies have verified that MSCs can be isolated from various adult tissues such as the bone marrow, adipose tissue, synovium, and neonatal tissues, including the umbilical cord (blood), placenta, amniotic fluid, and amniotic membrane, and possess the potential of differentiating into diverse cell lineages and tissues like bone, adipose tissue, cartilage, nerves, and liver, both in vivo and in vitro ( Gao et al, 2018 ; Sumer et al, 2018 ; Mathot et al, 2019 ; Gong et al, 2021 ; Li J. et al, 2021 ; Li Q. Y. et al, 2021 ; Ramesh et al, 2021 ; Souza et al, 2021 ; Zhu et al, 2021 ; Bian et al, 2022 ). Others have verified that MSC treatment holding promise exerts indirect therapeutic mechanisms such as anti-inflammation ( Huang et al, 2019 ), secretion of growth factors ( Tang W. et al, 2021 ; Ulpiano et al, 2021 ), and EVs ( Bang and Kim, 2022 ), which are associated with the recovery of damaged tissues.…”
Section: Different Sources Of Mesenchymal Stem Cells In Intracerebral...mentioning
confidence: 99%
“…Some studies have verified that MSCs can be isolated from various adult tissues such as the bone marrow, adipose tissue, synovium, and neonatal tissues, including the umbilical cord (blood), placenta, amniotic fluid, and amniotic membrane, and possess the potential of differentiating into diverse cell lineages and tissues like bone, adipose tissue, cartilage, nerves, and liver, both in vivo and in vitro ( Gao et al, 2018 ; Sumer et al, 2018 ; Mathot et al, 2019 ; Gong et al, 2021 ; Li J. et al, 2021 ; Li Q. Y. et al, 2021 ; Ramesh et al, 2021 ; Souza et al, 2021 ; Zhu et al, 2021 ; Bian et al, 2022 ). Others have verified that MSC treatment holding promise exerts indirect therapeutic mechanisms such as anti-inflammation ( Huang et al, 2019 ), secretion of growth factors ( Tang W. et al, 2021 ; Ulpiano et al, 2021 ), and EVs ( Bang and Kim, 2022 ), which are associated with the recovery of damaged tissues.…”
Section: Different Sources Of Mesenchymal Stem Cells In Intracerebral...mentioning
confidence: 99%
“…Regarding their last strategy, exosomes comprising mRNAs, miRNAs, cytokines, and growth factors are isolated, and their effects on the behavior of fibroblasts are evaluated. The use of exosomes also exerts promising clinical translation [ 11 ]. For example, transplantation of exosomes from the human umbilical cord blood plasma (UCB-Exos) accelerates cutaneous wound healing through miR-21-3p-mediated promotion of angiogenesis and fibroblast function [ 107 ].…”
Section: Materials In Scarless Wound Healingmentioning
confidence: 99%
“…Additionally, differentiation towards cancer-associated fibroblasts (CAFs) may have an adverse function in skin healing. Yet, given the rapid development of nanotechnology, the use of nanodrugs may facilitate scar-free wound healing [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strong paracrine capability of MSCs provides a new approach to tissue repair. 25 Previous studies reported that a combination of stem cells and vector biomaterials jointly constituted a growth pattern conformed to the internal environment of the human body; thus, greatly improving the survival rate and proliferation efficiency of MSCs, and significantly enhancing their secretory properties. 26 , 27 There have been a number of studies on the tissue engineering of vector biomaterials, mainly involving bio-ceramics, alginate, chitosan, and hydrogels.…”
Section: Discussionmentioning
confidence: 99%